A unique funerary and ritual complex at the border zone of the Northern and Eastern European Plains as a record of cultural and social changes at the turn of the Neolithic and Bronze Age - Dariusz Manasterski; Katarzyna Januszek; Aleksandra Cetwińska; Katarzyna Kwiatkowska (Documenta Praehistorica, 2023)
In the 3rd millennium BC, the area of the Masurian Lake District, located at the border zone of the North and Eastern European Plains, was still dominated by hunter-gatherers. It was then that the Late Neolithic farming and pastoralist communities reached the region, where cultural and social changes were initiated. Tracing these changes is possible through an analysis of the unique funerary and ritual complex on the island of Lake Lanskie. Burials of representatives of the elites of rankingcommunities from the Late Neolithic were found there, as well as the discontinuation of such burials in the Early Bronze Age, which has already been associated with egalitarian communities.